2012
DOI: 10.4028/www.scientific.net/amr.550-553.1871
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Crude Extract from Pomelo Peel Against <i>Staphylococcus aureus</i>

Abstract: The antimicrobial of crude extract from pomelo peel on Staphylococcus aureas was investigated. Four organic solvents including 95% ethanol, dichlorometane, hexane and ethyl acetate, were used to extract the crude extract from pomelo peel. The antimicrobial activity of the crude extract was evaluated by detection of clear zone of inhibition. The experimental results showed that yield of yield of 95% ethanol, dichlorometane, hexane and ethyl acetate crude extract were 0.46, 0.57, 0.25, and 0.19%, respectively. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…e results in this study are consistent with the results of Abirami et al [23], who reported that the crude extracts of pomelo peels using the conventional methanol extraction had antimicrobial activities of around 8 mm to 10 mm (including 5 mm paper disc) against S. aureus, S. typhi, and P. aeruginosa. Another research showed that the inhibition zone of the crude extracts using the conventional solvent extraction (dichloromethane, hexane, or ethyl acetate) was between 7.54 mm and 8.83 mm (including disc paper of 6 mm) against S. aureus [24]. us, the extraction techniques in this study using the combined enzyme and ultrasound treatment for extracting the bioactive compounds from the pomelo peels had more advantages with high antimicrobial activities and considered as the innovation green extraction technology without using toxic solvents.…”
Section: Antimicrobial Activities Of Extracts From Peels Of Differentmentioning
confidence: 99%
“…e results in this study are consistent with the results of Abirami et al [23], who reported that the crude extracts of pomelo peels using the conventional methanol extraction had antimicrobial activities of around 8 mm to 10 mm (including 5 mm paper disc) against S. aureus, S. typhi, and P. aeruginosa. Another research showed that the inhibition zone of the crude extracts using the conventional solvent extraction (dichloromethane, hexane, or ethyl acetate) was between 7.54 mm and 8.83 mm (including disc paper of 6 mm) against S. aureus [24]. us, the extraction techniques in this study using the combined enzyme and ultrasound treatment for extracting the bioactive compounds from the pomelo peels had more advantages with high antimicrobial activities and considered as the innovation green extraction technology without using toxic solvents.…”
Section: Antimicrobial Activities Of Extracts From Peels Of Differentmentioning
confidence: 99%
“…(2) Pomelo peel flavonoid core emulsion preparation: Fresh pomelo was washed and peeled, dried in the oven to a steady weight and then ground into milled powder. The powder was extracted with ethanol at a ratio of 1:10 for 48 h, and then heated in a thermostatic water bath at 60 °C for 6 h [44]. The extract was filtered with a filtering machine to obtain the flavonoids of pomelo peel, and then evaporated by rotary evaporation until no ethanol was precipitated.…”
Section: Preparation Of Microcapsulesmentioning
confidence: 99%
“…These components have broad-spectrum antibacterial effects, which can effectively inhibit the growth of various bacteria and fungi, and have broad application prospects. Aichayawanich et al used four organic solvents, namely, ethanol, dichloromethane, hexane, and ethyl acetate, to derive a crude grapefruit peel extract and proved that it could be used to inhibit Staphylococcus aureus [44]. Thavanapong et al obtained grapefruit peel oil extracted by cold pressing, vacuum steam distillation, and supercritical carbon dioxide extraction, and used it to prove that grapefruit oil and grapefruit extract have quite good antibacterial activity against Staphylococcus aureus [45].…”
Section: Introductionmentioning
confidence: 99%